Molecular Machines Regulating the Release Probability of Synaptic Vesicles at the Active Zone - Körber, Christoph; Kuner, Thomas (Frontiers in Synaptic Neuroscience, 2016)
The fusion of synaptic vesicles (SVs) with the plasma membrane of the active zone (AZ) upon arrival of an action potential (AP) at the presynaptic compartment is a tightly regulated probabil-istic process crucial for information transfer. The probability of a SV to release its transmitter content in response to an AP, termed release probability (Pr), is highly diverse both at the level of entire synapses and individual SVs at a given synapse. Differences in Pr exist between different types of synapses, between synapses of the same type, synapses originating from the same axon and even between different SV subpopulations within the same presynaptic terminal. The Pr of SVs at the AZ is set by a complex interplay of different presynaptic properties including the availability of release-ready SVs, the location of the SVs relative to the voltage-gated calcium channels (VGCCs) at the AZ, the magnitude of calcium influx upon arrival of the AP, the buffer-ing of calcium ions as well as the identity and sensitivity of the calcium sensor. These properties are not only interconnected, but can also be regulated dynamically to match the requirements of activity patterns mediated by the synapse. Here, we review recent advances in identifying mole-cules and molecular machines taking part in the determination of vesicular Pr at the AZ.